National Indexing Day, in the United Kingdom, Australia, New Zealand and South Africa. (September 2018) - Ellis, Ruth; Flath, Tordis; Quinn, Sherrey; Thomas, Elisabeth; Davis, Madeleine; Coe, Mary; Burger, Marlene
Abstract : National Indexing Day has grown considerably from its beginnings in the UK in 2017, and this year ANZSI, ASAIB and SI all scheduled events to celebrate the day (nominally 29 March, although ASAIB chose to mark it on a separate day for practical reasons). This roundup of news about the Day draws on contributions to the ANZSI Newsletter and SI's SIDelights (April 2018).